1998
DOI: 10.1021/jp9824609
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude Control of Chemical Waves in Catalytic Membranes. Asymmetric Wave Propagation between Zones Loaded with Different Catalyst Concentrations

Abstract: Chemical waves of the Belousov−Zhabotinsky type are studied applying bathoferroin catalyst fixed on a polysulfone membrane. A new method is developed to create contacting high- (H) and low-amplitude (L) regions for chemical waves. The amplitude is high in zones (H) loaded with high catalyst concentrations, and it is low in zones (L) loaded with low catalyst concentrations. An asymmetric wave propagation is found:  waves coming from region H can initiate waves in region L across the HL boundary with a higher fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Indeed, if the curvature is small enough then its effect can be neglected [32] (see Figure 2 therein). For the corresponding experimental studies, we refer to [33,34,[36][37][38] and for numerical simulations see [39]. Our simulations are in good accordance with these experiments, see Figures 5 (a), (b) and (c).…”
Section: Simulation Results Discussionsupporting
confidence: 84%
“…Indeed, if the curvature is small enough then its effect can be neglected [32] (see Figure 2 therein). For the corresponding experimental studies, we refer to [33,34,[36][37][38] and for numerical simulations see [39]. Our simulations are in good accordance with these experiments, see Figures 5 (a), (b) and (c).…”
Section: Simulation Results Discussionsupporting
confidence: 84%
“…The frequency change of chemical waves mentioned above is a result of the propagation failures of chemical waves at the gap. The propagation failures can be explained on the basis of a simplified picture based on the concept of refractoriness. , That means the success or failure of the chemical wave propagation can be explained by the next conditions:…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, biological systems are extremely inhomogeneous and have spatial structures. Recently, investigations on chemical waves in the presence of various inhomogeneities became active in order to provide some insights into the spatiotemporal pattern formations in biological systems. …”
Section: Introductionmentioning
confidence: 99%
“…Chemical waves propagating in Belousov−Zhabotinsky (BZ) solutions have been thought to be a convenient model of waves in biological excitable media such as heart muscles and brain tissues. Most of the basic properties of the chemical waves have been revealed by experimental and theoretical studies on the chemical waves observed in spatially uniform BZ solutions. Recently, the propagation of chemical waves in inhomogeneous BZ systems has also come to occupy an important position in studies on the chemical waves, because biological excitable media are clearly inhomogeneous. The effects of geometrical shapes 9-14 and inhomogeneity of refractoriness 15,16 or excitability 17,18 of the excitable BZ media on the chemical wave propagation can be investigated by using modified BZ systems with fixed catalysts.…”
Section: Introductionmentioning
confidence: 99%